Study of a single-frequency retrodirective system with a beam pilot signal using dual-mode dielectric resonator antenna elements. Issue 2 (16th May 2017) - Matsumuro, Takayuki; Ishikawa, Yohei; Mitani, Tomohiko; Shinohara, Naoki; Yanagase, Masashi; Matsunaga, Mayumi
Abstract : A terrestrial microwave power transmission system is considered as an effective method for collecting natural energy. In this system, frequency dependence of the refractive index and multipath propagation due to the ground surface poses problems. In the study, a single-frequency retrodirective system was proposed with a beam pilot signal using dual-mode dielectric resonator antenna elements. The results confirmed that the beam pilot signal radiated from the entire surface of the receiving antenna and accurately used the same propagation space as that of microwave power by beam propagation method simulation. A dual-mode dielectric resonator antenna was proposed as a common array antenna element for the beam pilot signal and microwave power. This involves a cross-shaped hemispherical dielectric resonator structure, and an isolation level exceeding 60 dB was experimentally measured between the orthogonal ports of the fabricated antenna. The dual-mode dielectric resonator antenna with an isolation exceeding 60 dB was successfully developed as an enabling device to realize a single-frequency retrodirective system with a beam pilot signal.